(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Apology exposes excuse as a false and vicious position of the individual, destroying society. Unlike her, the ancient apologia maintained a joint being without moral and psychological pressure on the subject of excuse. Apologia’s appeal to apology in the Western cultural tradition was the result of the historical process of rationalization and individualization of the ethics of justification, which led to the unsolvable problem of recognizing the Other as an ontological guarantor of social and personal being. In the culture of the nomads, the excuse did not threaten the community, but served as a moral condition for living together, enshrined in the norms of the nomadic right of the Kazakhs «Keshirimdi Bolu» and «Cisre tomatau» – the ability to forgive without long words of excuse. The purpose of the article was to distinguish between the concepts apologia and apologia as a cultural marker of the western and eastern (Kazakh-nomadic) types of ethics of excuse. The theoretical and methodological basis of the work was foreign and domestic studies of the foundations of sociality, ethics, specific issues of national culture. The authors used historical, analytical methods, as well as the principles of phenomenology and hermeneutics. Research materials can be applied in the scientific and pedagogical practice of higher education, in the development of educational technologies aimed at discussing the ethical and philosophical problems of modernity and national culture. Key words: apology, excuse, ethics, logos, nomadic law.